Resilience or Resignation : Facing Droughts and Floods in Rural, Poor Bolivia - World Bank Group (World Bank, Washington, DC, 2017)
Bolivia is a country with a vast geographical diversity, from a high plateau (altiplano) that reaches 3,000 meters above sea level to valleys at mid-altitude and tropical plains. During the last decade, the magnitude of Bolivia’s weather patterns has undergone significant changes; extreme rainfall, floods, landslides, and droughts have been pushing the poorest and most marginalized communities beyond their ability to respond. There is a considerable amount of literature documenting the consequences of weather shocks on income and poverty. The aim of this study is to supplement the quantitative evidence of the impact of droughts and floods on the welfare of Bolivian households by exploring the impacts of these severe weather events which affect psychological factors, that in turn are important when it comes to preventing and responding to these events. The study highlight the importance of considering these intangible elements that drive families’ decisions, in the context of designing policies for managing weather risk. Interventions and policies aimed at improving risk management in very poor communities should take into account the role of these internal factors in the reception and adoption of solutions, and in the likelihood that the investments can contribute to social mobility. The report is organized as follows: section one gives introduction. Section two gives a brief overview of the research methods used. The third section discusses the main findings related to immediate impacts (physical losses as well as services impacted), risk management, and the role of agency. Lastly, the fourth section presents the conclusions reached.